Keteladanan Yesus Kristus Berdasarkan Injil Yohanes Terhadap Kinerja Guru - Yusak Agus Setiawan (Pusat Riset dan Inovasi Nasional, 2024)
This article explores the exemplary nature of Jesus Christ as depicted in the Gospel of John, with an emphasis on aspects of leadership, teaching, and wisdom that can serve as examples for educators. Through a thorough examination of the Gospel text, this article illustrates how the attitudes, behaviors, and teachings of Jesus Christ provide a foundation for exemplary leadership that influences and inspires the teaching profession.